Development of the starting reaction of track and field sprinters using sensory-motor means - Vinogradova O.P.; Morozova L.V.; Melnikova T.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to substantiate the development of the starting reaction using sensory-motor means of special training for female sprinters. Methods and structure of the study. The pedagogical experiment involved female sprinters of the I sports category, CMS (n=10) at the age of 17,5±0,5 years. Temporary indicators of the starting reaction of female sprinters competing in running at a distance of 60 m were considered. A set of special exercises was developed aimed at improving the starting reaction (RT) indicator, and corrections were made to the educational and training process at the special preparatory stage of training female athletes. Results and conclusions. The starting reaction index decreased from 0,207±0,01 s to 0,164±0,01 s. Positive dynamics were achieved through targeted improvement of the neuromuscular response of female athletes. Mobilization stimuli of sensory-motor exercises ensure intensive functional changes in the neuro-functional sphere and improve the coordination structure of the starting actions of female sprinters.